ANALISIS TINGKAT KESUBURAN TANAH AREA REHABILITASI DAS DI DESA ASAM RANDAH KECAMATAN HATUNGUN KABUPATEN TAPIN - Annisa Anindya; Yusanto Nugroho; Ahmad Yamani; Yusuf Yuliadi (Universitas Lambung Mangkurat, 2026)
The objective of this study is to analyze the soil fertility level of the watershed rehabilitation area (DAS) in Asam Randah Village. Determination of the place of data sampling using purposive sampling, the use of purposive sampling techniques because not all samples have criteria that match the phenomenon under study. This research was carried out by soil fertility analysis with reference to the soil fertility table from the Bogor Soil Research Center, 1995. Knowing the level of soil fertility status requires analysis of KTK parameters, alkaline saturation, P2O5, K2O, and C-organic soil. Whole soil sampling is carried out at the soil surface of about 0-20 cm using a sample ring to analyze the physical properties of the soil (texture). Soil fertility status is categorized in medium, low, very low, and high classes determined by a combination of these parameter data. Based on the results of the laboratory analysis of soil texture, soil fertility in the Acid Randah Village Watershed Rehabilitation Area block IV has three soil fertility statuses, namely, low, medium, high assessment of land fertility status DAS Rehabilitation PT.Borneo Indobara Desa Asam Randah Blok IV fertility status is relatively low, low soil fertility occurs due to high rainfall in the area causing soil erosion, nutrient leaching and other biological conditions. The washing of nutrients causes the nutrients in the soil to decrease, this washing increases the concentration of hydrogen ions relative to alkaline ions, thus lowering the pH of the soil